Implementation of CLIL Program in Islamic Affiliated Primary School: Teaching Assistants Project - Rafika Rabba Farah; khoiriyah khoiriyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
English teaching at primary school needs some improvement, particularly in its giving exposure and contextualizing English content. Content and Language Integrated Learning (CLIL) approach can be an effective way to the success of English teaching at the primary school level. Thus, this community service aims at empowering SD Aisyiyah Kota Malang with teaching thematic lessons through CLIL concepts by infusing Islamic content. The strategies implemented were formulated in five stages: need analysis, professional development workshop to school teachers and teaching assistants, syllabus and material design, implementation, and evaluation. Results show that school teachers and teaching assistants were able to integrate CLIL approach observed from the syllabus and material design. Also, students were all enthusiastic and engaged during the classroom activities. This community service implies that teaching assistants can foster English learning engagement for primary school graders.